Deep learning-based response spectrum analysis method for building structures - Kim, Taeyong; Kwon, Oh Sung; Song, Junho (Earthquake Engineering and Structural Dynamics, 2024)
The response spectrum method has gained widespread acceptance in practical applications owing to its favorable compromise between accuracy and practical efficiency. The method predicts the peak responses of multi-degree-of-freedom (MDOF) systems by combining modal responses. The Square Root of the Sum of Squares (SRSS) and Complete Quadratic Combination (CQC) rules are commonly used for modal combinations. However, it has been widely known that these rules have limitations in accurately predicting responses influenced by higher modes and cross-modal correlations. To improve the accuracy of the response spectrum analysis method for building structures, this paper proposes a Deep learning-based modal Combination (DC) rule by introducing modal contribution coefficients predicted by a deep neural network (DNN) model. The DC rule enhances prediction accuracy by considering the characteristics of ground motion and the dynamic properties of a structural system. The DC rule provides more accurate predictions than the conventional rules, particularly for irregular response spectra and responses affected by higher modes. The efficiency and applicability of the DC rule are demonstrated by numerical investigations of multistory shear buildings and steel frame structures with regular and irregular shapes. The source codes, data, and trained models are available for download at https://github.com/tyongkim/ERD2.
Keywords: Analysis method; Building structure; Complete quadratic combinations; Deep learning-based modal combination; Higher mode; Multi degree-of-freedom; Response spectrum analyses (RSA); Square-root; Square-root-of-sum-of-square; Sums of squares; Complete Quadratic Combination; Deep learning-based modal Combination; multi-degree-of-freedom; response spectrum analysis; Square-Root-of-Sum-of-Squares